High Prevalence of Anemia in Children in Dharavi Locality of Mumbai: Possible Role of Homeopathy (Advancements in Homeopathic Research, 2022)
Background: Prevalence of Anemia is reported to be as high as about 90% in some segments of the population in India. Dharavi is arguably the largest slum in Asia. Due to its socioeconomic status, there is a possibility of malnutrition in this area. We have surveyed the area for the prevalence of anemia in Dharavi. Methods: The status was assessed with the help of Local Laboratories at Dharavi. Children from 5 to 15 years of age were surveyed from 7 different areas of Dharavi. Their name, age, gender, contact number and the hemoglobin level were collected in the survey and analysed based on WHO criteria of mild (11 – 11.4 g/ dL), moderate (8.1 – 10.9 g/dL) and severe anemia (
Keywords: Anemia; Dharavi; Children; Slum; Nutrition; India